A positive electrode material and its preparation method and application

By adopting a polycrystalline structure and self-covering layer design in the ternary positive electrode material, combined with sealing and pressurized heat treatment technology, the problems of degradation in circulation performance and increased gas production caused by unstable material structure are solved, and higher circulation performance and stability are achieved.

CN119181795BActive Publication Date: 2025-02-28TIANJIN GUOAN MGL NEW MATERIALS TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411698649.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The existing ternary positive electrode materials are unstable during charging and discharging, resulting in stress accumulation, microcracks, lattice oxygen escape and side reactions, thereby reducing the circulating performance of the battery and increasing circulating gas production.

Method used

A positive electrode material with a polycrystalline structure is used, which is formed by secondary particles formed by the accumulation of primary particles, and the surface of which is covered with a first cladding layer, and the primary particles have a self-covering layer, which is coated by sealing and pressurized heat treatment to enhance the oxidation and corrosion resistance of the material.

Benefits of technology

It improves the circulation performance and crystal phase structure stability of the positive electrode material, reduces the circulating gas production and surface residual alkali, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention provides a positive electrode material and a preparation method and application thereof. The positive electrode material includes secondary particles formed by the accumulation of primary particles; the surface of the secondary particles is coated with a first coating layer, and the primary particles include primary particles with a self-coating layer; wherein the average size of the primary particles is ≤500nm. The positive electrode material with a polycrystalline structure provided by the present invention is not only coated on the surface of the secondary particles, but the primary particles also have a self-coating layer. On the one hand, it has excellent antioxidant and corrosion resistance, which helps to reduce the side reactions between the positive electrode active material and the electrolyte and improve the cycle performance of the battery; on the other hand, it helps to suppress the stress and strain of the matrix particles, inhibit the release of oxygen and the dissolution of transition metals, prevent the formation of CEI and the deconstruction of the near-surface structure, and improve the crystalline phase structure stability of the positive electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a positive electrode material and a preparation method and application thereof. Background Art

[0002] In recent years, the new energy vehicle industry has developed rapidly, and consumers have put forward higher requirements for the cruising range of new energy vehicles, which requires further improvement of the energy density of power batteries. In power lithium-ion batteries, the positive electrode material plays a decisive role in the energy density of lithium-ion batteries. Currently, the commercially available positive electrode materials for power lithium-ion batteries mainly include ternary materials, lithium iron phosphate and spinel lithium manganese oxide. Among them, the theoretical specific capacity of ternary materials can reach 275mAh / g, and the specific capacity of commercial high-nickel ternary materials can reach more than 200mAh / g; the theoretical specific capacity of lithium iron phosphate is 170mAh / g, and the actual specific capacity is 150mAh / g-160mAh / g; the theoretical specific capacity of spinel lithium manganese oxide is 148mAh / g, and the actual specific capacity is 130mAh / g-140mAh / g. Therefore, to achieve high energy density of power batteries, ternary materials are undoubtedly the best choice for positive electrode materials.

[0003] At present, ternary positive electrode materials can be divided into single crystal and polycrystalline based on crystal morphology. Polycrystalline is a secondary large particle formed by the agglomeration of small single crystal particles, which has a higher discharge capacity and first cycle efficiency. However, during the charge and discharge process of ternary polycrystalline positive electrode materials, the unit cell volume will change greatly, resulting in stress accumulation causing microcracks and lattice oxygen escape; the electrolyte will enter the material along the cracks, resulting in the generation of positive electrode-electrolyte interface side reactions, triggering surface phase changes, increasing impedance, and greatly reducing the cycle performance of the material; and lattice oxygen escape will accelerate the decomposition of the electrolyte and form a thicker CEI film. The degradation of the CEI film and the unstable interface structure during the charge and discharge process lead to cyclic gas production, which is one of the reasons for the failure of the positive electrode; especially with the increase of nickel content in the ternary positive electrode material, the amount of residual alkali on the surface increases, the water absorption of the material becomes stronger, and the high-valent nickel ions (Ni 4+ ) will induce the production of singlet oxygen, which will further oxidize EC to generate CO2, CO and H2O. The presence of water will also promote the hydrolysis reaction of EC to release CO2. During high-temperature cycling, the reaction kinetics of gas release will be accelerated, causing serious attenuation of battery performance.

[0004] Regarding the structural stability of ternary positive electrode materials, the main measures currently adopted are to improve the stability of the material body and interface structure by ion doping, secondary particle surface coating, adding multiple sintering processes or water washing processes to remove surface foreign matter. For doped materials, cracks will still appear after long-term cycles; for secondary particle surface coating materials, it only improves the stability of the interface between the secondary particle surface and the electrolyte, and once cracks appear, the new primary particles and the electrolyte interface will still have side reactions, resulting in decreased cycle performance; and for the formation of CEI membranes, the existing technology uses an additional water washing process to remove surface foreign matter and prevent the formation of unstable CEI. Although the above-mentioned improvement methods are effective, their effectiveness is limited because they may lead to loss of specific capacity, reduce interface conductivity, and the process is relatively complex and the processing cost is high.

[0005] Therefore, how to improve the cycle stability of ternary positive electrode materials and reduce cycle gas production is a technical problem that needs to be solved urgently. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a positive electrode material and a preparation method and application thereof. The positive electrode material with a polycrystalline structure provided by the present invention is not only coated on the surface of the secondary particles, but the primary particles also have a self-coating layer. On the one hand, it has excellent antioxidant and corrosion resistance, which helps to reduce the side reactions between the positive electrode active material and the electrolyte and improve the cycle performance of the battery; on the other hand, it helps to suppress the stress and strain of the matrix particles, inhibit the release of oxygen and the dissolution of transition metals, prevent the formation of CEI and the deconstruction of the near-surface structure, and improve the crystalline phase structure stability of the positive electrode active material.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a positive electrode material, wherein the positive electrode material is a polycrystalline structure, and the positive electrode material comprises secondary particles formed by stacking primary particles; the surface of the secondary particles is coated with a first coating layer, and the primary particles comprise primary particles having a self-coating layer;

[0009] Wherein, the average size of the primary particles is ≤500nm, for example, 50nm, 75nm, 100nm, 125nm, 150nm, 175nm, 200nm, 225nm, 250nm, 275nm, 300nm, 325nm, 350nm, 375nm, 400nm, 425nm, 450nm, 475nm or 500nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0010] It should be noted that the average size of the primary particles in the present invention refers to the average particle size of a single fine grain; and the primary particles are primary grains, that is, the smallest unit particles without stacking, flocculation and other structures.

[0011] The method for measuring the average size of the primary particles in the present invention is: a field emission scanning electron microscope FESEM is exposed at a magnification of 30K to collect cross-sectional measurement results of particles with obvious boundaries within the visual range, and the average value of multiple measurement results is obtained, which is the specific value of the average size of the primary particles.

[0012] The positive electrode material with a polycrystalline structure provided by the present invention is a secondary particle obtained by piling up primary particles with an average size of ≤500nm. The particle structure is stable and the mechanical properties are high. The first coating layer on the surface of the secondary particles and the self-coating layer in the primary particles have excellent antioxidant and corrosion resistance, which helps to reduce the side reaction between the positive electrode material and the electrolyte and improve the cycle performance of the battery. On the other hand, the positive electrode material is coated both from the inside and the surface, which helps to inhibit the stress and strain of the primary particles and the secondary particles in the positive electrode material, delay the expansion of microcracks, inhibit the release of oxygen and the dissolution of transition metals, prevent the formation of CEI and the deconstruction of the near-surface structure, and improve the stability of the crystal phase structure of the positive electrode material. The corrosion resistance of the interface structure is improved. Even if the first coating layer is broken, the self-coating layer in the primary particles can still play a good isolation effect, thereby improving the capacity and cycle performance of the positive electrode material and reducing the problems of residual alkali and gas production on the surface of the positive electrode material.

[0013] In the present invention, if only the first coating layer is coated on the surface of the secondary particles, it is impossible to solve the problem that during a long cycle, once cracks are generated, new primary particles will be exposed to the electrolyte, and the side reactions with the electrolyte will be aggravated, resulting in a decrease in cycle performance; and if the average size of the primary particles is too large, exceeding 500nm, it will seriously affect the lithium ion deintercalation, resulting in low capacity and poor rate performance. Therefore, the positive electrode material with a polycrystalline structure provided by the present invention, the self-coating layer of the primary particles, the first coating layer of the secondary particles and the average size of the primary particles must cooperate with each other, and none of them can be missing, so as to improve the room temperature and high temperature cycle performance of the positive electrode material and reduce the gas production during the cycle without affecting the capacity.

[0014] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0015] Preferably, the cathode material has a spherical and / or spherical-like morphology.

[0016] Preferably, the primary particles having the self-coating layer are located on the surface layer of the secondary particles.

[0017] Preferably, the thickness of the secondary particles of the primary particles having a self-coating layer is 0.5~2μm, for example 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm or 2μm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] The positive electrode material provided by the present invention performs self-coating of primary particles near the surface of secondary particles (the thickness of the secondary particles of the primary particles with the self-coating layer is 0.5~2μm), which can effectively inhibit the corrosion of the electrolyte on the near-surface structure and improve the corrosion resistance and oxidation resistance of the positive electrode material interface.

[0019] Preferably, the D50 of the secondary particles is 5-20 μm, for example 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] In a second aspect, the present invention provides a method for preparing the positive electrode material as described in the first aspect, the preparation method comprising the following steps:

[0021] Mixing the positive electrode material to be coated, the coating agent and hydrogen peroxide, and performing a sealing, pressurizing and heat treatment to obtain the positive electrode material;

[0022] Wherein, the positive electrode material to be coated includes secondary particles formed by accumulation of primary particles.

[0023] It should be noted that the present invention does not specifically limit the specific preparation process of the sealing and pressurizing heat treatment, and the present invention is applicable to all preparation methods that can achieve the sealing and pressurizing function.

[0024] The preparation method provided by the present invention uses sealed pressurized treatment, and hydrogen peroxide generates oxygen under the action of high temperature and high pressure, thereby increasing the oxygen partial pressure in the sealed space, reducing the lithium-nickel mixing in the positive electrode material, and also serving as the melting diffusion power of the coating agent, promoting the uniform diffusion of the coating agent along the grain boundary, thereby realizing the self-coating of primary particles in the positive electrode material and the surface coating of secondary particles, and the water generated during the reaction can be used to dissolve the residual alkali on the surface, so there is no need to perform additional water washing treatment on the positive electrode material; and this process does not require the additional addition of a catalyst, etc., the product is easy to separate, has fewer impurities, and has the advantages of simple preparation process, low cost, convenient operation, and a large controllable range.

[0025] In the present invention, if the sealing and pressurizing treatment is not performed, the coating agent cannot be dissolved, and the hydrogen peroxide cannot be decomposed to generate oxygen partial pressure, which is not conducive to the occurrence of the self-coating reaction of the primary particles, and ultimately causes the electrical properties of the positive electrode material to deteriorate.

[0026] Preferably, in the mixed solution, the solid-liquid mass ratio is 1:(0.1~1.5), for example 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4 or 1:1.5, etc., wherein the solid content is the sum of the masses of the positive electrode material and the coating agent, and the masses of the liquid and the solid are both g, but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] In the present invention, in the mixed solution, the hydrogen peroxide in the hydrogen peroxide is dissolved in the solution, and the positive electrode material to be coated and the coating agent are dispersed in the solution as solid substances; and the mixed solution in the present invention refers to a uniformly mixed solution before reaction.

[0028] Preferably, the mass ratio of the added amount of the coating agent to the positive electrode material is (0.0019~0.02):1, for example 0.0019:1, 0.002:1, 0.005:1, 0.008:1, 0.01:1, 0.013:1, 0.015:1, 0.018:1 or 0.02:1, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] In the present invention, by regulating the solid-liquid mass ratio of the mixed solution to be 1: (0.1-1.5) and / or the mass ratio of the added amount of the coating agent to the positive electrode material to be (0.0019-0.02): 1, the added amount of hydrogen peroxide and the positive electrode material is regulated, which is more conducive to achieving self-coating of primary particles in the positive electrode material and surface coating of secondary particles.

[0030] Preferably, the mixed raw materials further include a solvent.

[0031] In the present invention, in order to control the solid-liquid ratio in the mixed solution, a solvent can be adaptively added for adjustment, and the present invention does not specifically limit the specific material type of the solvent. The present invention is applicable to conventional solvent types that can be used for liquid phase coating and will not react, including but not limited to ethanol.

[0032] Preferably, the temperature of the sealing pressurized heat treatment is 50~500℃, for example, 50℃, 75℃, 100℃, 125℃, 150℃, 175℃, 200℃, 225℃, 250℃, 275℃, 300℃, 325℃, 375℃, 400℃, 425℃, 450℃, 475℃ or 500℃, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] Preferably, the sealing and pressurized heat treatment time is 10 to 36 hours, for example 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, 24 hours, 25 hours, 27 hours, 30 hours, 35 hours or 36 hours, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] Preferably, the method for preparing the positive electrode material to be coated comprises:

[0035] The positive electrode precursor material and the lithium source are mixed and sintered to obtain the positive electrode material to be coated.

[0036] Preferably, the sintering temperature is 650~1000℃, for example, 650℃, 675℃, 700℃, 725℃, 750℃, 775℃, 800℃, 825℃, 850℃, 875℃, 900℃, 925℃, 950℃, 975℃ or 1000℃, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] Preferably, the sintering time is 8 to 20 hours, for example 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours or 20 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] In the preparation process of the positive electrode material to be coated provided by the present invention, a treatment process such as water washing is required after sintering, that is, the sintered product is the positive electrode material to be coated.

[0039] It should be noted that, in the preparation method of the positive electrode material to be coated provided by the present invention, the preparation method of the positive electrode precursor material and the like are all conventional technical solutions, and those skilled in the art can make adaptive selections and adjustments according to actual needs;

[0040] Optionally, during the preparation of the positive electrode material to be coated, a dopant, such as a metal oxide dopant or a non-metallic dopant, may be added, or bulk doping may be performed during the preparation of the positive electrode precursor material, which may also be purchased directly;

[0041] Optionally, the positive electrode precursor material may be a hydroxide precursor material, a carbonate precursor material or an oxide precursor material, etc.;

[0042] Optionally, the lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium nitrate or lithium acetate.

[0043] As a preferred technical solution, the preparation method comprises the following steps:

[0044] Mixing the positive electrode precursor material and the lithium source, sintering at 650-1000° C. for 3-20 hours, and obtaining the positive electrode material to be coated, which is composed of secondary particles accumulated from primary particles;

[0045] The positive electrode material to be coated, the coating agent, hydrogen peroxide and the solvent are mixed, and the solid-liquid ratio in the mixed solution is 1: (0.1-1.5), wherein the solid content is the sum of the masses of the positive electrode material and the coating agent; the mass ratio of the added amount of the coating agent to the positive electrode material is (0.0019-0.02): 1, and the mixture is sealed and pressurized for heat treatment at 50-500°C for 10-36h to obtain the positive electrode material;

[0046] Wherein, the positive electrode material to be coated includes secondary particles formed by accumulation of primary particles.

[0047] It should be noted that the positive electrode material to be coated provided by the present invention is a conventional layered transition metal oxide material containing nickel, and the present invention is applicable to positive electrode materials that can be obtained within a reasonable range by those skilled in the art;

[0048] Exemplarily, the present invention provides a positive electrode material with the general chemical formula Li k Ni x A y B zO2, wherein 1≤k≤1.1, 0<x<1, 0<y<1, 0≤z<1, and x+y+z≤1, A includes at least one of Mn, Al or Co, and B includes a transition metal element, wherein B includes but is not limited to at least one of S, P, F, B, N, Al, Ti, Mg, Zr, V, Nb, Y, W, Ta, Co, Ce, Na or Zn;

[0049] For example, the k may be 1, 1.02, 1.03, 1.05, 1.08 or 1.1, the x may be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.95 or 0.99, the y may be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.95 or 0.99, and the z may be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.95 or 0.99, etc.;

[0050] Furthermore, when the positive electrode material to be coated provided by the present invention is a high-nickel positive electrode material or an ultra-high-nickel positive electrode material, that is, 0.8≤x<1, the effect of suppressing cyclic gas generation is more excellent.

[0051] It should also be noted that the present invention does not specifically limit the specific material type of the coating agent. The present invention is applicable to conventional coating agent materials used for coating positive electrode materials. For example, the coating agent includes a compound of at least one element selected from Al, Ti, Mg, Zr, Nb, W, Ta or Co.

[0052] In a third aspect, the present invention further provides a lithium ion battery, wherein the lithium ion battery comprises the positive electrode material as described in the first aspect or the positive electrode material prepared by the preparation method as described in the second aspect.

[0053] Compared with the prior art, the present invention has the following beneficial effects:

[0054] (1) The positive electrode material with a polycrystalline structure provided by the present invention is a secondary particle obtained by piling up primary particles with an average size of ≤500nm. The particle structure is stable and the mechanical properties are high. The first coating layer on the surface of the secondary particles and the self-coating layer in the primary particles have excellent antioxidant and corrosion resistance, which helps to reduce the side reaction between the positive electrode material and the electrolyte and improve the cycle performance of the battery. On the other hand, the positive electrode material with a polycrystalline structure is coated both from the inside and the surface, which helps to suppress the stress and strain of the primary particles and secondary particles in the positive electrode material, suppress the release of oxygen and the dissolution of transition metals, prevent the formation of CEI and the deconstruction of the near-surface structure, and improve the stability of the crystal phase structure of the positive electrode material. In addition, the corrosion resistance of the interface structure is improved. Even if the first coating layer is broken, the self-coating layer in the primary particles can still play a good insulation effect, thereby improving the capacity and cycle performance of the positive electrode material and reducing the problems of residual alkali and gas production on the surface of the positive electrode material.

[0055] (2) The preparation method provided by the present invention, through sealed pressurized treatment, hydrogen peroxide produces oxygen under high temperature and high pressure, thereby increasing the oxygen partial pressure in the sealed space, reducing the lithium nickel mixing in the positive electrode material, and serving as the melting diffusion power of the coating agent, promoting the uniform diffusion of the coating agent along the grain boundary, thereby achieving the self-coating of the primary particles in the positive electrode material and the surface coating of the secondary particles. The water generated during the reaction can be used to dissolve the residual alkali on the surface, so there is no need to perform additional water washing treatment on the positive electrode material. Moreover, this process does not require the addition of additional catalysts, etc., the product is easy to separate, has fewer impurities, and has the advantages of simple preparation process, low cost, convenient operation, and a wide controllable range. DETAILED DESCRIPTION

[0056] The technical scheme of the present invention is further illustrated by specific examples below. Those skilled in the art should understand that the examples are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0057] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions. Example 1

[0058] This embodiment provides a polycrystalline positive electrode material, the polycrystalline positive electrode material includes secondary particles formed by stacking primary particles; the surface of the secondary particles is coated with a first coating layer, and the primary particles include primary particles with a self-coating layer;

[0059] The D50 of the secondary particles is 17 μm, the average size of the primary particles is 500 nm, and the primary particles having the self-coating layer are located on the surface of the secondary particles and have a thickness of 1 μm.

[0060] The preparation method of the polycrystalline positive electrode material is as follows:

[0061] (1) Take 150g of ternary cathode material precursor Ni 0.90 Co 0.06 Mn 0.04 (OH)2 and 69.157g of lithium hydroxide, 0.5927g of ZrO2, 0.4350g of Al2O3, and 0.4545g of SrCO3 were mixed evenly, and the mixed materials were placed in a sintering furnace with an oxygen ventilation rate of 5m 3 / h, firstly heating to 660℃ for 6h, then heating to 785℃ for 9h, and then cooling naturally and hand-sifting through a 300-mesh sieve to obtain the sintered product, which is the positive electrode material to be coated;

[0062] (2) 150 g of the sintered product obtained in step (1), 0.75 g of H3BO3, and 0.42 g of Al2O3 were added with 151.17 g of hydrogen peroxide so that the solid-liquid ratio in the mixed solution was 1:1, and the mixed solution was transferred into a high-temperature pressurized self-sufficient container, which was sealed and placed in an oven and kept at 150°C for 10 h. The high-temperature pressurized self-sufficient container was then taken out and cooled. The high-temperature pressurized self-sufficient container was opened, the reactants were centrifuged, and the sample was washed with ethanol to obtain a black precipitate, which was then vacuum dried to obtain the polycrystalline positive electrode material. Example 2

[0063] This embodiment provides a polycrystalline positive electrode material, the polycrystalline positive electrode material includes secondary particles formed by stacking primary particles; the surface of the secondary particles is coated with a first coating layer, and the primary particles include primary particles with a self-coating layer;

[0064] The D50 of the secondary particles is 13.5 μm, the average size of the primary particles is 380 nm, and the primary particles having the self-coating layer are located on the surface of the secondary particles and have a thickness of 1.5 μm.

[0065] The preparation method of the polycrystalline positive electrode material is as follows:

[0066] (1) Take 150g of ternary cathode material precursor Ni 0.90 Co 0.06 Mn 0.04(OH)2 and 69.157g of lithium hydroxide, 0.5927g of ZrO2, 0.4350g of Al2O3, and 0.4545g of SrCO3 were mixed evenly, and the mixed materials were placed in a sintering furnace with an oxygen ventilation rate of 5m 3 / h, firstly heating to 625℃ for 6h, then heating to 750℃ for 9h, and then naturally cooling down and hand-sieving through a 300-mesh sieve to obtain the sintered product, which is the positive electrode material to be coated;

[0067] (2) Add 211.215 g of hydrogen peroxide to 140 g of the sintered product obtained in step (1), 0.40 g of Al(OH)2, 0.21 g of Co(OH)2, and 0.20 g of Nb2O5, so that the solid-liquid ratio in the mixed solution is 1:1.5, transfer the mixed solution into a high-temperature pressurized self-sufficient container, seal the high-temperature pressurized self-sufficient container, put it into an oven, and keep it at 200°C for 20 h, then take out the high-temperature pressurized self-sufficient container, cool it, open the high-temperature pressurized self-sufficient container, centrifuge the reactants, wash the sample with ethanol to obtain a black precipitate, and then vacuum dry it to obtain the polycrystalline positive electrode material. Example 3

[0068] This embodiment provides a polycrystalline positive electrode material, the polycrystalline positive electrode material includes secondary particles formed by stacking primary particles; the surface of the secondary particles is coated with a first coating layer, and the primary particles include primary particles with a self-coating layer;

[0069] The secondary particles have a D50 of 5.0 μm, the average size of the primary particles is 100 nm, and the primary particles having the self-coating layer are located on the surface of the secondary particles and have a thickness of 2 μm.

[0070] The preparation method of the polycrystalline positive electrode material is as follows:

[0071] (1) Take 150g of ternary cathode material precursor Ni 0.90 Co 0.06 Mn 0.04 (OH)2 and 69.157g of lithium hydroxide, 0.5927g of ZrO2, 0.4350g of Al2O3, and 0.4545g of SrCO3 were mixed evenly, and the mixed materials were placed in a sintering furnace with an oxygen ventilation rate of 5m 3 / h, firstly heating to 595°C for 6h, then heating to 720°C for 9h, and then cooling naturally and hand-sifting through a 300-mesh sieve to obtain the sintered product, which is the positive electrode material to be coated;

[0072] (2) 150 g of the sintered product obtained in step (1) was mixed with 0.12 g of ZrO2, 1.42 g of Co(OH)2, and 0.25 g of Nb12 WO 33 , add 15.18g of hydrogen peroxide and an appropriate amount of ethanol and mix evenly so that the solid-liquid ratio in the mixed solution is 1:0.1, transfer the mixed solution into a high-temperature pressurized self-sufficient container, seal the high-temperature pressurized self-sufficient container, put it into a muffle furnace, and keep it at 500°C for 10 hours, then take out the high-temperature pressurized self-sufficient container, after cooling, open the high-temperature pressurized self-sufficient container, centrifuge the reactants, wash the sample with ethanol to obtain a black precipitate, and then vacuum dry it to obtain the polycrystalline positive electrode material. Example 4

[0073] The difference between this embodiment and embodiment 1 is that the D50 of the secondary particles in this embodiment is 13.5 μm.

[0074] The preparation method step (1) is regulated as follows: 150 g of ternary cathode material precursor Ni 0.90 Co 0.06 Mn 0.04 (OH)2 and 69.157g of lithium hydroxide, 0.5927g of ZrO2, 0.4350g of Al2O3, and 0.4545g of SrCO3 were mixed evenly, and the mixed materials were placed in a sintering furnace with an oxygen ventilation rate of 5m 3 / h, first raise the temperature to 645℃ and sinter for 6h, then raise the temperature to 770℃ and sinter for 9h. After natural cooling, sieve through a 300-mesh sieve by hand to obtain the sintered product, which is the positive electrode material to be coated.

[0075] The rest of the preparation methods and parameters were the same as those in Example 1. Example 5

[0076] The difference between this embodiment and embodiment 1 is that the average size of the primary particles of the polycrystalline positive electrode material in this embodiment is 350 nm.

[0077] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the temperature is kept at 100° C. for 10 h.

[0078] The rest of the preparation methods and parameters were the same as those in Example 1. Example 6

[0079] The difference between this embodiment and embodiment 1 is that the chemical formula of the ternary positive electrode material precursor in this embodiment is Ni 0.8 Co 0.1 Mn 0.1 (OH)2.

[0080] The rest of the preparation methods and parameters were the same as those in Example 1. Example 7

[0081] The difference between this embodiment and embodiment 1 is that in the mixed solution in step (2) of this embodiment, the solid-liquid ratio is 1:0.05.

[0082] The rest of the preparation methods and parameters were the same as those in Example 1. Example 8

[0083] The difference between this embodiment and embodiment 1 is that in the mixed solution in step (2) of this embodiment, the solid-liquid ratio is 1:2.

[0084] The rest of the preparation methods and parameters were the same as those in Example 1.

[0085] Comparative Example 1

[0086] The difference between this comparative example and Example 1 is that in the polycrystalline positive electrode material provided in this comparative example, only the surface of the secondary particles is coated with the first coating layer, and the primary particles do not contain a self-coating layer;

[0087] In the preparation method, the sintered product obtained in step (1) is washed with water, dried, filtered, and dried to obtain the positive electrode material to be coated;

[0088] In step (2), 150 g of the dried product was mixed with 0.75 g of H3BO3 and 0.42 g of Al2O3, and after mixing evenly, the mixture was stirred at an oxygen flow rate of 5 m 3 / h, sintering was carried out, the temperature was raised to 280°C and sintering was carried out for 6h, and after natural cooling, the sintering product was sieved through a 300-mesh sieve by hand to obtain the polycrystalline positive electrode material.

[0089] The rest of the preparation methods and parameters were the same as those in Example 1.

[0090] Comparative Example 2

[0091] The difference between this comparative example and Example 1 is that the average size of the primary particles in this comparative example is 600 nm;

[0092] In the preparation method, in step (1), the sintering curve is adjusted to first increase the temperature to 625°C for sintering for 6 hours, and then increase the temperature to 850°C for sintering for 9 hours. After natural cooling, the sintered product is hand-sieved through a 300-mesh sieve to obtain the positive electrode material to be coated.

[0093] The rest of the preparation methods and parameters were the same as those in Example 1.

[0094] Comparative Example 3

[0095] The difference between this comparative example and Example 1 is that in this comparative example, the mixed solution in step (2) is placed in an open crucible and heat treated in a non-sealed environment.

[0096] The rest of the preparation methods and parameters were the same as those in Example 1.

[0097] Comparative Example 4

[0098] The difference between this comparative example and Example 3 is that in the polycrystalline positive electrode material provided in this comparative example, only the surface of the secondary particles is coated with the first coating layer, and the primary particles do not contain a self-coating layer;

[0099] In the preparation method, the sintered product obtained in step (1) is washed with water, dried, filtered, and dried to obtain the positive electrode material to be coated;

[0100] In step (2), 140 g of the positive electrode material to be coated obtained in step (1) is dry-mixed with 0.40 g of Al(OH)2, 0.21 g of Co(OH)2, and 0.20 g of Nb2O5. After mixing evenly, the mixture is heated under an oxygen ventilation rate of 5 m 3 / h, sintering is carried out, the temperature is raised to 600°C and sintering is carried out for 6 hours, and after natural cooling, the sintering product is sieved through a 300-mesh sieve by hand to obtain the polycrystalline positive electrode material.

[0101] The rest of the preparation methods and parameters were the same as those in Example 3.

[0102] Comparative Example 5

[0103] The difference between this comparative example and Example 4 is that in the polycrystalline positive electrode material provided in this comparative example, only the surface of the secondary particles is coated with the first coating layer, and the primary particles do not contain a self-coating layer;

[0104] In the preparation method, the sintered product obtained in step (1) is washed with water, dried, filtered, and dried to obtain the positive electrode material to be coated;

[0105] Take 150g of the dried product and dry mix it with 0.75g of H3BO3 and 0.42g of Al2O3. After mixing evenly, stir in an oxygen ventilation volume of 5m 3 / h, sintering was carried out, the temperature was raised to 280°C and sintering was carried out for 6h, and after natural cooling, the sintering product was sieved through a 300-mesh sieve by hand to obtain the polycrystalline positive electrode material.

[0106] The remaining preparation methods and parameters were consistent with those in Example 4.

[0107] The polycrystalline positive electrode materials provided in Examples 1-8 and Comparative Examples 1-5 were tested for surface residual alkali. The test conditions were as follows: 3.0±0.05 g of sample was weighed into a 250 mL beaker, 100 mL of ultrapure water was added using a measuring cylinder, a magnet was placed, and the sample was placed on a magnetic stirrer. The stirring speed was adjusted so that the sample was stirred in a vortex shape. After sufficient stirring for 3 minutes, the sample was allowed to stand. After the solution was separated into layers, all the supernatant was filtered into a 300 mL conical flask, and the filtrate was transferred to a 250 mL large beaker. The original conical flask was washed three times with ultrapure water. Finally, the filtrate transferred to the beaker was placed on a potentiometric titration table and titrated with a 0.14 mol / L hydrochloric acid standard solution. The test results are shown in Table 1.

[0108] The polycrystalline positive electrode materials provided in Examples 1-8 and Comparative Examples 1-5 were used to prepare battery structures and the electrochemical performance of the batteries was tested.

[0109] (a) Button cell preparation:

[0110] The positive electrode material, conductive carbon black and binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 90:5:5, and N-methylpyrrolidone (NMP) was used as a solvent to obtain a positive electrode slurry, which was evenly coated on an aluminum foil, vacuum dried at 100 °C for 8 h, and rolled to obtain a compacted density of 2.0 g / cm 3 , surface density is 9g / cm 2 The positive electrode;

[0111] A lithium sheet was used as the counter electrode, and a porous polypropylene membrane (Celgard2400) was used as a separator to separate the positive electrode and the counter electrode. The composition of the electrolyte was: a mixture of 1 mol / L LiPF6 and EC, DMC and EMC (EC:DMC:EMC volume ratio = 1:1:1). The CR2032 button battery was assembled in an argon glove box.

[0112] (b) Full cell preparation:

[0113] Preparation of positive electrode sheets: The prepared positive electrode material: PVDF:CNT:SP is dissolved in NMP in a mass ratio of NCM:PVDF:CNT:SP = 97.00%:1.30%:0.50%:1.20%, and stirred into a paste slurry. The slurry is then coated on a 15 μm thick aluminum foil current collector using a transfer machine, dried in an oven at 70°C-75°C, and roll-formed, and cut into positive electrode sheets of the required size.

[0114] Preparation of negative electrode sheet: Graphite: SP: CMC: SBR is dissolved in deionized water in a mass ratio of 94.5%: 1%: 1.5%: 2.0%, and stirred into a paste slurry. Then the obtained slurry is coated on a 9μm thick copper foil current collector by a coating machine, dried in an oven at 115℃, and rolled into shape, and cut into negative electrode sheets of the required size. The ear is welded, and the electrode sheet is baked in an oven at 120℃ for 20h. Battery assembly: The positive electrode sheet, the separator PP, and the negative electrode sheet are wound into the required battery cell, wrapped with aluminum plastic film, and continued to be baked for 48h after the short circuit test. After the moisture is qualified, the injection, exhaust, sealing, pre-charging, formation, aging and other processes are carried out to obtain the required battery, wherein the composition of the injected electrolyte is: The composition of the electrolyte is: a mixture of 1mol / L LiPF6 and EC, DMC and EMC (EC: DMC: EMC volume ratio = 1:1:1).

[0115] Battery performance test:

[0116] The batteries provided in Examples 1-8 and Comparative Examples 1-5 were subjected to performance tests:

[0117] (a) Button battery cycle performance test: The capacity was tested at a rate of 0.2C and the capacity retention rate was tested at 1C / 1C for 50 cycles.

[0118] (b) Full battery cycle gas production test: high temperature , 0.5C / 1C initial volume V1, 100 cycles volume V2, volume growth rate (V2-V1) / V1.

[0119] The test results of the above batteries are also shown in Table 1.

[0120] Table 1

[0121]

[0122] From Table 1, we can get:

[0123] From the data results of Examples 1-6, it can be seen that the preparation method provided by the present invention is applicable to positive electrode materials with various nickel contents, thereby improving the capacity and cycle performance of positive electrode materials with different nickel contents and reducing the residual alkali on the surface of the positive electrode material, thereby reducing gas production.

[0124] From the data results of Example 1, Example 7 and Example 8, it can be seen that by adjusting the solid-liquid ratio in the mixed solution to 1: (0.1~1.5), it is more conducive to achieving the self-coating of primary particles and the surface coating of secondary particles in the polycrystalline positive electrode material, while too low or too high solid-liquid ratio is not conducive to the self-coating of primary particles and the surface coating of secondary particles in the present invention. From Example 7, it can be seen that if the solid-liquid ratio is too low, the self-coating of primary particles and the surface coating of secondary particles will be affected, resulting in a decrease in the capacity and cycle performance of the positive electrode material, an increase in residual alkali, and an increase in gas production. From Example 8, it can be seen that if the solid-liquid ratio is too high, although the residual alkali content is reduced, the interface of the secondary particles of the material is destroyed, resulting in a decrease in the capacity and cycle performance of the positive electrode material and an increase in gas production.

[0125] From the data results of Example 1 and Comparative Example 1, Example 3 and Comparative Example 4, and Example 4 and Comparative Example 5, it can be seen that the preparation method provided by the present invention is not used to achieve self-coating of the primary particles, and only the surface coating of the secondary particles is performed, which leads to a significant decrease in the capacity and cycle of the positive electrode material, and a significant increase in residual alkali and gas production.

[0126] From the data results of Example 1 and Comparative Example 2, it can be seen that if the average size of the primary particles is too large, it will seriously affect the lithium ion deintercalation distance of the polycrystalline positive electrode material, resulting in reduced capacity and cycle, and also lead to serious deterioration of the self-coating of the primary particles and the surface coating of the secondary particles, thereby causing a significant increase in the cyclic gas production of the positive electrode material.

[0127] It can be seen from the data results of Example 1 and Comparative Example 3 that in the preparation method provided by the present invention, if the coating reaction is not carried out in a closed environment, a polycrystalline positive electrode material structure with primary particle self-coating and secondary particle surface coating cannot be obtained.

[0128] In summary, the preparation method provided by the present invention, through the sealed pressurized treatment, hydrogen peroxide generates oxygen under the action of high temperature and high pressure, thereby increasing the oxygen partial pressure in the sealed space, reducing the lithium nickel mixing in the positive electrode material, and also serving as the melting diffusion power of the coating agent, promoting the uniform diffusion of the coating agent along the grain boundary, thereby realizing the self-coating of the primary particles and the surface coating of the secondary particles in the positive electrode material with a polycrystalline structure. The first coating layer on the surface of the secondary particles and the self-coating layer in the primary particles have excellent antioxidant and corrosion resistance, which helps to reduce the side reactions between the positive electrode material and the electrolyte. On the one hand, the positive electrode material is coated from the inside and the surface, which helps to suppress the stress and strain of the primary and secondary particles in the positive electrode material, suppress the release of oxygen and the dissolution of transition metals, prevent the formation of CEI and the deconstruction of the near-surface structure, and improve the crystalline structure stability of the positive electrode material; and improve the corrosion resistance of the interface structure. Even if the first coating layer is broken, the self-coating layer in the primary particles can still play a good isolation effect, thereby improving the capacity and cycle performance of the positive electrode material and reducing problems such as residual alkali and gas production on the surface of the positive electrode material.

[0129] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A positive electrode material, characterized in that: The positive electrode material is a polycrystalline structure, and the positive electrode material includes secondary particles formed by stacking primary particles; the surface of the secondary particles is coated with a first coating layer, and the primary particles include primary particles with a self-coating layer; Wherein, the average size of the primary particles is ≤500nm; The positive electrode material is prepared by the following preparation method, which comprises the following steps: Mixing the positive electrode material to be coated, the coating agent and hydrogen peroxide, and performing a sealing, pressurizing and heat treatment to obtain the positive electrode material; Wherein, the positive electrode material to be coated includes secondary particles formed by accumulation of primary particles.

2. The positive electrode material according to claim 1, characterized in that The primary particles having the self-coating layer are located on the surface of the secondary particles; And / or, the thickness of the secondary particles of the primary particles having a self-coating layer is 0.5 to 2 μm.

3. The positive electrode material according to claim 1 or 2, characterized in that The D50 of the secondary particles is 5-20 μm.

4. A method for preparing a positive electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: Mixing the positive electrode material to be coated, the coating agent and hydrogen peroxide, and performing a sealing, pressurizing and heat treatment to obtain the positive electrode material; Wherein, the positive electrode material to be coated includes secondary particles formed by accumulation of primary particles.

5. The preparation method according to claim 4, characterized in that: In the mixed solution, the solid-liquid mass ratio is 1:(0.1-1.5), wherein the solid content is the sum of the masses of the positive electrode material to be coated and the coating agent; The mass ratio of the added amount of the coating agent to the positive electrode material of the layer to be coated is (0.0019~0.02):1; The mixed raw materials further include a solvent. When the mixed raw materials include a solvent, the mixed solution includes the positive electrode material to be coated, a coating agent, hydrogen peroxide and the solvent.

6. The preparation method according to claim 4, characterized in that: The temperature of the sealing and pressurizing heat treatment is 50-500° C., and the time of the sealing and pressurizing heat treatment is 10-36 hours.

7. The preparation method according to claim 4, characterized in that: The method for preparing the positive electrode material to be coated comprises: The positive electrode precursor material and the lithium source are mixed and sintered to obtain the positive electrode material to be coated.

8. The preparation method according to claim 7, characterized in that: The sintering temperature is 650-1000° C., and the sintering time is 3-20 hours.

9. The preparation method according to claim 4, characterized in that: The preparation method comprises the following steps: Mixing the positive electrode precursor material and the lithium source, sintering at 650-1000° C. for 3-20 hours, and obtaining the positive electrode material to be coated, which is composed of secondary particles accumulated from primary particles; The positive electrode material to be coated, the coating agent, hydrogen peroxide and the solvent are mixed, and the solid-liquid ratio in the mixed solution is 1: (0.1-1.5), wherein the solid content is the sum of the masses of the positive electrode material and the coating agent; the mass ratio of the added amount of the coating agent to the positive electrode material is (0.0019-0.02): 1, and the mixture is sealed and pressurized for heat treatment at 50-500°C for 10-36h to obtain the positive electrode material; The positive electrode material to be coated includes secondary particles formed by accumulation of primary particles, and the mixed solution includes the positive electrode material to be coated, a coating agent, hydrogen peroxide and a solvent.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode material according to any one of claims 1 to 3 or the positive electrode material prepared by the preparation method according to any one of claims 4 to 9.

Citation Information

Patent Citations

  • Method for realizing uniform coating of surfaces of primary particles and obtained positive electrode material

    CN115863653A